The relationships between work-family conflict and life satisfaction and happiness among nurses: a moderated mediation model of gratitude and self-compassion - El Keshky, Mogeda El Sayed; Sarour, Enas ObaidAllah (Frontiers in Public Health, 2024)
Background: Changing gender roles in the workplace have resulted in increased work-family conflict. Researchers and practitioners are concerned with this issue given thatthe impact of work-family conflict negatively impactson the well-being of workers, including those in the health care sector, and previous research suggested that nurses were experiencing a range of negative outcomes. Aim: To investigate the potentially mediating role of self-compassion and moderating role of gratitude in the relationships between work-family conflict and both life satisfaction and happiness among Saudi nurses.